The magnetic permeability signature in high-frequency electromagnetic data modeling: a case study for GPR approximation - Sánchez, Alejandra I.; Gallardo, Luis A. (Frontiers in Earth Science, 2025)
Ground penetrating Radar (GPR) is a high-frequency geophysical prospecting method whose signal is affected by dielectric permittivity (ε), electrical conductivity (σ) and magnetic permeability (μ), but it is common practice to assume that magnetic permeability has a negligible influence on electromagnetic (EM) fields in geophysical applications. In this paper, we analyze the distinctive effect of magnetic permeability on the radar signal. To evaluate the transit of an electromagnetic wave, we developed a finite-difference time-domain (FDTD) algorithm that accounts for ε−,μ−, and σ− heterogeneities. Using a hypothetical coupled-layer model and an archaeological test example, we demonstrate the importance of considering magnetic permeability in numerical EM modeling, concluding that magnetic permeability is as relevant as the other property variations and also is the only property that simultaneously affects the velocity and attenuation of the electromagnetic wave and produces a unique energy partition unpredicted by any combination of the other two EM properties.